The effect of type of sound damper material in the Helmholtz resonator to the output power spectrum of acoustic energy Harvester - Hedwigis Harindra; Agung Bambang Setio Utomo; Ikhsan Setiawan (Universitas Sebelas Maret, 2019)
Acoustic energy harvesting is one of many ways to harness acoustic noises as wasted energy into useful electical energy using an acoustic energy harvester. Acoustic energy harvester that tested by Dimastya (2018) which is consisted of loudspeaker and Helmholtz resonator, produced two-peak spectrum. It is suspected that the first peak is due to Helmholtz resonator resonance and the second peak comesfrom the resonance of the conversion loudspeaker. This research is to experimentally confirm the guess of the origin of the first peak. The experiments are performed by adding silencer materials on the resonator inner wall which are expected to be able to reduce the height of first peak and to know how they affect the output electric power spectrum of the acoustic energy harvester. Three different silencer materials are used, those are glasswool, acoustic foam, and styrofoam, with the same thickness of 12 cm. The results show that glasswool absorbs sound more effectively than acostic foam and styrofoam. The use of glasswool, acoustic foam, and styrofoam with 12 cm thickness lowered the first peak by 90% (from 39 mW to 0,5 mW), 82% (from 39 mW to 0,7 mW), and 82% (from 39 mW to 0,7 mW), respectively. Based on these results, it is concluded that the guess of the origin of the first peak is confirmed.